Integrating Kashmir: Modernity, Development and Sedimented Narratives - Iymon Majid (American Journal of Islam and Society)
How to make sense of the politics and history of Kashmir since decolonization? Two new important books deal with this question and provide a detailed account of what is/was happening in Kashmir—one of the most densely militarized regions in the world with a long history of a self-determination movement. For many years now, and these two books are part of that conversation, scholars have centered Kashmir in their analysis instead of fixating on the dispute between India and Pakistan or the internationalisation of the conflict. This change has brought new perspectives and conceptual categories to study the region. This is a much-needed corrective especially considering that scholarly work on Kashmir has relied on the ‘nation-state’ framework for too long.